CHARACTERISTICS OF NASOPHARYNGEAL CARSINOMA IN CHILDREN AND ADOLESCENTS IN DR. ZAINOEL ABIDIN GENERAL HOSPITAL BANDA ACEH - Lily Setiani; Fadhlia; Benny Kurnia; Yerni Karnita (TALENTA PUBLISHER, 2019)
Introduction: Nasopharyngeal Carcinoma (NPC) is a malignant tumor arising from epithelial cells that cover the nasopharynx. NPC is a rare malignancy in children. The incidence of NPC varies by age, geographical and ethnic factors which indicate both genetic and environmental factors contribute to the tumor growth. NPC in children has several features different from adults. Objective: To assess characteristics of nasopharyngeal carcinoma in children and adolescents in dr. Zainoel Abidin general hospital Banda Aceh from 2014-2019. Methods: The study was conducted in dr. Zainoel Abidin general hospital Banda Aceh. This study is a descriptive with cross sectional retrospective design. The data collected from medical records of patients diagnosed with nasopharyngeal carcinoma from January 2014-September 2019. The variable including regional distribution, gender, age (between 0-25 years), histopathologic types, stage and chemotherapy regimen used. The sampling was done by total sampling method. Results: The result showed that there was 17 patients of nasopharyngeal carcinoma in children and adolescents with the highest case came from Bireuen and North Aceh district 3 (17.7%) patients, respectively. South Aceh and West Aceh distric 2 (11.8%) patients, respectively. Nasopharyngeal carcinoma mostly infected 9 (53%) male patients than 8 (47%) female with a sex ratio of 1.1 : 1. The age most affected is at the end of childhood between 17-25 years had 9 (53%) patients and between 12-16 years had 8 (47%) patients with the average age range was 17.2 years (range 13-22 years). Most of histopathologic types had found in the type of undifferentiated carcinoma (WHO type III) as many as 7 (41.1%) patients with stage IV being the most frequent 9 (53%) patients. The most widely used chemotherapy regimen is a combination of Cisplatin and Docetaxel with 10 (62.5%) patients. Conclusion: Nasopharyngeal carcinoma in children generally occur at the end of childhood with the most common type of undifferentiated carcinoma (WHO type III) and stage IV which associated with advanced locoregional disease and higher rates of distant metastasis.